Evaluation of Decellularized Bovine Tendon Sheets for Achilles Tendon Defect Reconstruction in a Rabbit Model. Issue 11 (September 2018) - Zhang, Cheng-Hao; Jiang, Yan-Lin; Ning, Liang-Ju; Li, Qi; Fu, Wei-Li; Zhang, Ya-Jing; Zhang, Yan-Jing; Xia, Chun-Chao; Li, Jian; Qin, Ting-Wu
Background: Achilles tendon (AT) defects frequently occur in trauma and chronic injuries. Currently, no method can satisfactorily reconstruct the AT with completely restored function. Purpose: To evaluate the postoperative outcomes of AT defect reconstruction with decellularized bovine tendon sheets (DBTSs) in a rabbit model. Study Design: Controlled laboratory study. Methods: DBTSs were prepared from bovine tendons after compression, decellularization, antigen extraction, freeze drying, and sterilization. Platelet-rich plasma (PRP) was obtained by differential centrifugation. Sixty-three rabbits were used in this study, and the AT defect model was created bilaterally. All rabbits were divided into 3 groups (n = 21). In the DBTS group and the DBTS + PRP group, 2-cm-long AT was excised and reconstructed by DBTSs or PRP-treated DBTSs. In the control group, the rabbits underwent AT transection, and stumps were sutured. After surgery, all rabbits were assessed by ultrasonography and magnetic resonance imaging and then sacrificed for histological examination and biomechanical testing at 4, 8, or 12 weeks. Results: Gross observations demonstrated the absence of immunologic incompatibility and rejection. Histological examination showed that DBTSs promoted host cell infiltration and new fibrous tissue integration as compared with the control group. In each group, there was an AT-like structure formation and aligned collagen fiber deposition at 12 weeks. Mechanical properties of the reconstructed AT were not significantly different among the 3 groups at 4, 8, and 12 weeks after surgery ( P > .05). Ultrasonography and magnetic resonance imaging results illustrated that the reconstructed AT from each group maintained remodeling, and there was no significant difference in the echogenicity scoring ( P > .05) and percentages of good and excellent ( P > .05) among the 3 groups. Conclusion: DBTSs, which retain the native tendon structure and bioactive factors, had the ability to remodel and integrate into the rabbit AT and improve the healing process. Clinical Relevance: DBTSs could serve as an effective bioscaffold to reconstruct AT defects.